COVID-19 Outbreak: Routes of Transmission, Precautions, and Economic Impact on Dentistry-A Review Article - Tahir Abdalqadir, Mohammed (Kurdistan Journal of Applied Research, 2020)
In late 2019, a novel coronavirus appeared in Wuhan, Hubei province, China, and then rapidly spread around the world. The virus produces severe and even fatal pneumonia; the most common clinical symptoms among infected persons include fever, shortness of breath, cough, fatigue, and abnormal chest CT. Though the virus first traveled from animal to human, it can now spread from human to human through direct transmission such as coughing, sneezing, and inhalation of droplets; and through contact with mucus membranes of oral, nasal, and eye. COVID-19 also can be transmitted through saliva and the fecal–oral route. The risk of cross-infection between patients and dental practitioners is high due to the nature of dental work, so this outbreak has made a powerful impact, both medically and economically, on the dentistry sector. Dental practitioners should have comprehensive knowledge of the virus and its route of transmission, and they should take proper precautions during dental treatments to protect themselves and their patients. This article provides a review of COVID-19, its transmission routes, necessary precautions during dental setting, and the virus’s impact on the economy of the dental industry.